Implementation of Relevant Methods in Assessing Traffic-Technological Projects - Barić, Danijela; Čurepić, Danko; Radačić, Željko (Promet - Traffic&Transportation)
The assessment of investment traffic-technological projectsmeans a set of activities whose basic aim is to determine the justificationand feasibility of the projects. The decision-makingprocess, including the decision-making on investments is an extremelycomplex process, and the decision-maker has to have avision of the future and make decisions accordingly in a modemand flexible manner. Therefore, the decisions need to be theresult of a planning and research process based on relevant scientificmethods. The work includes the selected, analysed andpresented methods of cost-benefit analysis, methods of multi-criteria decision-making and SWOT (Strengths, Weaknesses,Opportunities, and Threats) analysis methods. Regarding thebasic characteristics, the mentioned methods have been compared,the order of their implementation has been determined,and then they have been implemented in assessing the traffic-technological projects of reconstmction with the aim of selectingthe optimal variant solution.